The Hummingbird Project: A Positive Psychology Intervention for Secondary School Students - Platt, Ian Andrew; Kannangara, Chathurika; Tytherleigh, Michelle; Carson, Jerome (Frontiers in Psychology, 2020)
Mental health in schools has attracted a lot of attention in recent years. Positive Psychology Interventions (PPIs) in secondary schools have been shown to improve mental health outcomes for students. Previous PPIs have tended to be delivered by trained Psychology specialists or have tended to focus on a single aspect of Positive Psychology such as Mindfulness. The current study involved 4 phases. Phases 1 and 2 were scoping studies involving semi-structured interviews with educators. Educators believed that deprivation and lack of funding for intervention in mental health were the main drivers of mental ill-health. They also felt that, whilst well placed to identify need for mental intervention, they are unable to intervene in student mental health. Phase 3 piloted a PPI, delivered by current university students in Psychology, which educated secondary school students (N = 90) in a variety of Positive Psychology concepts. Phase 4 involved delivering the PPI to secondary school students (N = 1,054). This PPI, the Hummingbird Project, led to improvements in student well-being, as measured by the World Health Organization Well-Being Index (WHO-5). The intervention also led to improvements in student resilience, as measured by the Bolton Uni-Stride Scale (BUSS), and hope, as measured by the Children's Hope Scale (CHS). Improvements were also found in students' confidence in their own use of the concepts covered in the intervention, as measured by the Hummingbird Life Satisfaction Scale (HLSS). Results are discussed in the context of their implications for the future of psychological intervention in secondary school settings.